The cicada genus Semia Matsumura, 1917 (Hemiptera: Cicadidae) from Vietnam, with new records and a key to species - Thai, Pham Hong; Constant, Jérôme (Academia Journal of Biology, 2014)
The genus Semia Matsumura that is from East Asia. According to Lee & Hill, 2010, this genus belongs to subtribe Psithyristriina within the tribe Cicadini. There are six species S. watanabei (Matsumura),  S. klapperichi Jacobi, S. lachna Lei & Chou, S. majuscula Distant, S. spinosa Pham, Hayashi & Yang, and S. gialaiensis Pham & Constant. A revised description of the cicada species Semia watanabei (Matsumura, 1907) is provided. A key to the four Vietnamese Semia species: S. majuscula (Distant), S. watanabei (Matsumura), S. spinosa Pham, Hayashi & Yang, and S. gialaiensis Pham & Constant is provided. Synonymic lists and new locality records for the four species of Semia from Vietnam are provided.